(untitled) (Baghdad Science Journal, 2019)
Ag2O (Silver Oxide) is an important p-type (in chasm to most oxides which were n-type), with a high conductivity semiconductor. From the optical absorbance data, the energy gap value of the Ag2O thin films was 1.93 eV, where this value substantially depends on the production method, vacuum evaporation of silver, and optical properties of Ag2O thin films are also affected by the precipitation conditions. The n-type and p-type silicon substrates were used with porous silicon wafers to precipitate ±125 nm, as thick Ag2O thin film by thermal evaporation techniques in vacuum and via rapid thermal oxidation of 400oC and oxidation time 95 s, then characterized by measurement of XRD, optical properties and scanning electron microscopy properties (SEM). Maximum value of photo response obtained from p-Ag2O/p-PS/Si photodetector results revealed two peak sat 600 nm and 800 nm. According to the x-ray diffraction four peaks appear, (111), (200), (110) and (311) Ag, respectively, (polycrystalline film) and lattice constant of (4.077 Å). Also the results showed a sharp increasing in the absorption-wave length plot of Ag2O film at UV and IR regions. The accumulation of the stars-like are semi-regular of the Ag2O nanocrystals on the surface of p-type PS and the other diffuse inside the pores in a nearly uniform distribution with a different grain size on the surface. The results of the dislocation density and strain are decreased with the grain size increasing.